Design of a Modular Revetment Using Recycled Tires for Coastal Protection Mitigation at Amal Baru Beach, Tarakan (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
Costal abrasion in Tarakan City requires a protection system that is not only structurally effective but also economically feasible and implementable through community-based approaches. This study aims to design a modular revetment structure using recycled tires filled with concrete and compacted sand based on a design-based analytical approach. Wave transformation analysis at a depth of -0.52 meters indicates significant wave heights ranging from 1.19 to 1.70 meters, which serve as the primary basis for stability calculations using the Hudson formula with a conservative stability coefficient 1.25. The results show that a single concrete-filled tire unit weighs approximately 285 kg, and five units are required to form the primary armor layer with a height of 1.20 meters. To achieve the design crest elevation of +1.95 meters relative to HHWL, additional secondary protection layers and a toe protection system made of quarry stones were incorporated, resulting in a total structural height of 2.40 meters. Sensitivity analysis indicates that variations in significant wave height strongly influence the required weight of armor, whereas changes in material density produce more moderate effects. Compared with conventional stone revetments, the modular tire system offers greater flexibility, ease of installation without heavy equipment, and supports circular-economy principles through the reuse of waste tires. The implementation plan adopts a participatory appriach by engaging local fishermen and coastal communities in material collection, assembly, and maintenance activities. This study provides a sustainable, low-cost, and adaptive alternative for coastal protection that can be replicated in other shoreline areas with similar environment conditions.
Keywords: Abrasion; Coastal; Modular; Perticipatory; Revetment; Structure